Abdominal Wall Pain or Irritable Bowel Syndrome: Validation of a Pediatric Questionnaire. Issue 3 (September 2019) - Siawash, Murid; van Assen, Tijmen; Tjon a Ten, Walther; Janssen, Loes; van Heurn, Ernst; Roumen, Rudi; Scheltinga, Marc
ABSTRACT: Objectives: A questionnaire study demonstrated that some adult patients who were diagnosed with irritable bowel syndrome (IBS) were in fact having an abdominal wall pain syndrome, such as anterior cutaneous nerve entrapment syndrome (ACNES). The aim of the present study was to investigate whether a pediatric version of this questionnaire was useful in diagnosing abdominal wall pain syndromes in children with chronic abdominal pain (CAP). Methods: An 18-item questionnaire was tested in 3 groups of children with CAP: group 1, children who underwent surgery for ACNES (n = 42); group 2, children who were found to have ACNES after an outpatient analysis (n = 57); and group 3, children diagnosed with IBS (n = 53). Qualities including internal consistency (Cronbach α), cut-off points and a ROC-curve were calculated using standard statistical analysis. Results: Questionnaire response rates in the three populations of CAP children ranged from 69% to 92%. When comparing ACNES and IBS groups, 17 of 18 questions were discriminative ( P  < 0.01, Cronbach α 0.74). Total questionnaire scores ranged from 0 (IBS likely) to 17 points (ACNES likely). A median 13-point score (range 8–17) was found in both ACNES groups. In contrast, a median 8-point score was calculated in children with IBS (range 3–13, P  < 0.01). Using an 11-point cut-off score, a child with CAP was diagnosed with ACNES with 86% sensitivity and 89% specificity. A ROC curve with an AUC of 0.94 was obtained. Conclusions: A 17-item questionnaire showed good diagnostic test properties and may aid in distinguishing ACNES from IBS in pediatric populations with chronic abdominal pain. Abstract : Supplemental Digital Content is available in the text